Analisis Dampak Pertambangan Tanpa Izin (PETI) Batu Andesit di Desa Tasikmalaya Kabupaten Rejang Lebong - Radeni ILyan Putra; Risna Armalia; Eva Satriani; Reflis Reflis; Satria P Utama (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
The Unlicensed Mining Activity (PETI) andesite stone in Tasikmalaya Village, Rejang Lebong Regency, has had a significant impact on the local environment, social, and economy. This study aims to assess the environmental degradation caused by PETI, such as changes in topography, damage to vegetation, and water and air pollution. Spatial analysis based on satellite images showed an increase in mining land area from 2.98 hectares in 2014 to 4.51 hectares in 2024, with a growth rate of about 0.45 hectares per year. From the social side, PETI activities cause land conflicts and create economic dependence of the community on the illegal mining sector, although it provides a relatively higher daily income than the agricultural sector. However, PETI does not contribute to local revenue, even potentially causing tax losses of up to Rp240 million per year. This study uses qualitative, quantitative, and spatial approaches through interviews, field observations, and satellite image analysis. The proposed policy recommendations include the legalization of PETI through the establishment of people's mining areas (WPR), rehabilitation of degraded land, strengthening village institutions, and the development of economic alternatives to reduce community dependence on illegal mining. This finding confirms the importance of sustainable management of Natural Resources in order to minimize the negative impact of crates on the environment and society.